Graphene‐polymer nanocomposites for biomedical applications. (28th September 2017) - Silva, Magda; Alves, Natália M.; Paiva, Maria C.
Abstract : Despite the significant efforts in the synthesis of new polymers, the mechanical properties of polymer matrices can be considered modest in most cases, which limits their application in demanding areas. The isolation of graphene and evaluation of its outstanding properties, such as high thermal conductivity, superior mechanical properties, and high electronic transport, have attracted academic and industrial interest, and opened good perspectives for the integration of graphene as a filler in polymer matrices to form advanced multifunctional composites. Graphene‐based nanomaterials have prompted the development of flexible nanocomposites for emerging applications that require superior mechanical, thermal, electrical, optical, and chemical performance. These multifunctional nanocomposites may be tailored to synergistically combine the characteristics of both components if proper structural and interfacial organization is achieved. The investigations carried out in this aim have combined graphene with different polymers, leading to a variety of graphene‐based nanocomposites. The extensive research on graphene and its functionalization, as well as polymer graphene composites, aiming at applications in the biomedical field, are reviewed in this paper. An overview of the polymer matrices adequate for the biomedical area and the production techniques of graphene composites is presented. Finally, the applications of such nanocomposites in the biomedical field, particularly in drug delivery, wound healing, and biosensing, are discussed.